Generalization and False Memory in an Acquired Equivalence Paradigm: The Influence of Physical Resemblance Across Related Episodes - Bowman, Caitlin R.; de Araujo Sanchez, Maria-Alejandra; Hou, William; Rubin, Sarina; Zeithamova, Dagmar (Frontiers in Psychology, 2021)
The ability to make inferences about related experiences is an important function of memory that allows individuals to build generalizable knowledge. In some cases, however, making inferences may lead to false memories when individuals misremember inferred information as having been observed. One factor that is known to increase the prevalence of false memories is physical resemblance between new and old information. The extent to which physical resemblance has parallel effects on generalization and memory for the source of inferred associations is not known. To investigate the parallels between memory generalization and false memories, we conducted two experiments using an acquired equivalence paradigm and manipulated physical resemblance between items that made up related experiences. Three experiments showed increased generalization for higher levels of resemblance. Recognition and source memory judgments revealed that high rates of generalization were not always accompanied by high rates of false memories. Thus, physical resemblance across episodes may promote generalization with or without a trade-off in terms of impeding memory specificity.